Budidaya Tanaman Hortikultura dan Lumbung Pangan dalam Upaya Pemanfaatan Lahan Pekarangan di Kelurahan Klitren Yogyakarta - Galuh Banowati; Rina Ekawati; Lestari Hetalesi Saputri; Hartini Hartini; Ratna Sri Harjanti; Retno Muningsih (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
One of the characteristics of urban areas is the increasingly limited land that can be used for plant cultivation. Only now, a lot of yard land has yet to be utilized optimally, especially for cultivating vegetables. Klitren Village, in the center of Yogyakarta City, has community-owned yard land that can be used even though the area is limited. This service activity aims to maximize the use of yard land for cultivating vegetable plants, herbal gardens, and food storage. This service activity was carried out in Klitren Village at the Asoka Farming Women's Group (FWG) in July 2022. The service activity was attended by 81 people who were a combination of women members of Asoka's FWG, the Village Head of Klitren Village, Village Agricultural Extension Officers, Lecturers, Students, Research and Community Service Units, and the Klitren Village community from various. The service is carried out through several activities, including making planting media for cultivating vegetable plants, arranging herbal gardens, and providing food barns. 100% of the evaluation results stated that the activity participants knew how to make planting media and food storage. In comparison, 66.7% said they knew how to organize and maintain an herbal garden. 66.7% of the participant's responses to the activities indicated that they were helpful and hoped they could be sustainable and improved.